Adjusted Model for the Completeness of National Cancer Incidence Estimates - Kamo, Ken-ichi; Yanagihara, Hirokazu (Journal of the Japan Statistical Society, Japanese Issue, 2025)
This paper focuses on the mathematical method which evaluates the completeness for estimation of nationwide cancer incidence in Japan. The information for national cancer incidence is currently reported by the National Cancer Registry, but it was previously estimated based on regional cancer registry. It has been pointed out that regional cancer registry contains registration omissions, which may have provided the underestimate for the national incidence. Then, in this paper, we focus on the statistical method, which is based on binomial regression model with indices of completeness, to estimate the completeness of registration. The method was applied to the 2015 data and estimate the registration rate.